(3JQLeI cJGH GdfaS dCQSWhs
(3ChdgG (B:s
(3gPG eG PcQ GdajdSha ai cJGH GdfaS JQLefGg cdGekG JGekG hPcQfG ai cd HGH Led eG QO Ydi ef NGda bhdg s
(3BNQgG (B:s
(3abW GdHUQ hGdSeY bgGJGf GdMGTjJGf CcQe ef SGFQ GdMhGS JeJ GdebGdI hJe GdcJGH hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde JSdjekG Edi jhe GdOjf s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(649/3) s
Keywords: (3GdadSaI hGdefWbs